Impact of sensor-based wastewater irrigation on chemical soil health in chrysanthemum (Chrysanthemum morifolium) - ANKIT,; GURJAR, D S; ROSIN, K G; SHEKHAWAT, KAPILA; JAIN, RITU (The Indian Journal of Agricultural Sciences, 2023)
A field experiment was conducted to study the short-term impact of sensor-based wastewater irrigation scheduling on chemical soil health in chrysanthemum (Chrysanthemum morifolium Ramat.) at Water Technology Centre, ICAR-Indian Agricultural Research Institute (IARI), New Delhi during 2019–20. Experiment was conducted with following 6 treatments, viz. T1, Groundwater irrigation (GWI) at 25% Maximum Allowable Depletion (MAD), T2, GWI at 50% MAD, T3, GWI at 75% MAD, T4, Wastewater irrigation (WWI) at 25% MAD, T5, WWI at 50% MAD, T6, WWI at 75% MAD and was laid out in a randomized block design (RBD) in open field condition with 4 replications. Soil samples and quality of groundwater and wastewater were assessed during and after the experiment to quantify the chemical properties (pH, EC and OC), primary nutrients (NPK), micronutrients (Fe, Mn, Cu and Zn) and heavy metals (Ni, Pb, Cr and Cd). Results shows that pH and EC remains the same. Organic carbon, primary nutrient and micronutrients content significantly increased in wastewater irrigated soils and best result was observed in T5. Moreover, the content of heavy metals (Ni, Cr, Cd and Pb) in soils was significantly not changed with different wastewater irrigation treatments. Wastewater irrigation have beneficial impacts on soil chemical parameters in terms of higher amount of organic matter, primary and micronutrients in soil.